2022
DOI: 10.1002/slct.202200605
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal‐ and Oxidant‐Free Regioselective Synthesis of 3,4,5‐Trisubstituted Pyrazoles by Means of [3+2] Cycloaddition Reactions

Abstract: A highly efficient regioselective synthesis of 3,4,5-trisubstituted pyrazoles via transition metal-and oxidant-free, three component [3 + 2] cycloaddition with thiazolidinedione chalcones, benzaldehydes and N-tosylhydrazine is described. The reaction proceeds through CÀ C and CÀ N bond formations under mild reaction conditions to produce structurally diverse polysubstituted pyrazoles in moderate to good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Allakaet al reported the regioselective synthesis of 3,4,5trisubstituted pyrazole derivatives 315 via [3 + 2] cycloaddition reaction (Scheme 59). [77] This MCR was performed by reacting thiazolidinedione chalcones 314, benzaldehydes 1 and Ntosylhydrazinein presence of Cs 2 CO 3 in DMF at 100 °C. Under mild reaction condition the reaction proceeds through CÀ C and CÀ N bond formations and produced structurally diverse pyrazole derivatives 315 in moderate to good yields.…”
Section: Synthesis Of Pyrazolesmentioning
confidence: 99%
“…Allakaet al reported the regioselective synthesis of 3,4,5trisubstituted pyrazole derivatives 315 via [3 + 2] cycloaddition reaction (Scheme 59). [77] This MCR was performed by reacting thiazolidinedione chalcones 314, benzaldehydes 1 and Ntosylhydrazinein presence of Cs 2 CO 3 in DMF at 100 °C. Under mild reaction condition the reaction proceeds through CÀ C and CÀ N bond formations and produced structurally diverse pyrazole derivatives 315 in moderate to good yields.…”
Section: Synthesis Of Pyrazolesmentioning
confidence: 99%
“…37–41 Here in, we report ionic liquid mediated and ultrasound assisted, one-pot multicomponent synthesis of 1,3-diphenylpyrazole- based spirooxindolopyrrolizidines via [3+2]-cycloaddition and their in vitro anti-TB activity. 42,43…”
Section: Introductionmentioning
confidence: 99%
“…The [3+2] cycloaddition process is a highly regio-selective approach for the synthesis of spiroxindoles. 12,13,14,15 Spirooxindole alkaloids found in nature, such as horsfiline, extracted from Horsfieldia superba are used in traditional medicine (Figure 1). 16,17 However, the spiroxindoles having 1,2,4-oxadiazole ring systems are rare in the literature.…”
Section: Introductionmentioning
confidence: 99%